RETRACTED: Mitochondrial Fission and Mitophagy Reciprocally Orchestrate Cardiac Fibroblasts Activation - Gao, Qing-Yuan; Zhang, Hai-Feng; Tao, Jun; Chen, Zhi-Teng; Liu, Chi-Yu; Liu, Wen-Hao; Wu, Mao-Xiong; Yin, Wen-Yao; Gao, Guang-Hao; Xie, Yong; Yang, Ying; Liu, Pin-Ming; et al. (Frontiers in Cell and Developmental Biology, 2021)
Although mitochondrial fission has been reported to increase proliferative capacity and collagen production, it can also contribute to mitochondrial impairment, which is detrimental to cell survival. The aim of the present study was to investigate the role of mitochondrial fission in cardiac fibroblasts (CF) activation and explore the mechanisms involved in the maintenance of mitochondrial health under this condition. For this, changes in the levels of mitochondrial fission/fusion-related proteins were assessed in transforming growth factor beta 1 (TGF-β1)-activated CF, whereas the role of mitochondrial fission during this process was also elucidated, as were the underlying mechanisms. The interaction between mitochondrial fission and mitophagy, the main defense mechanism against mitochondrial impairment, was also explored. The results showed that the mitochondria in TGF-β1-treated CF were noticeably more fragmented than those of controls. The expression of several mitochondrial fission-related proteins was markedly upregulated, and the levels of fusion-related proteins were also altered, but to a lesser extent. Inhibiting mitochondrial fission resulted in a marked attenuation of TGF-β1-induced CF activation. The TGF-β1-induced increase in glycolysis was greatly suppressed in the presence of a mitochondrial inhibitor, whereas a glycolysis-specific antagonist exerted little additional antifibrotic effects. TGF-β1 treatment increased cellular levels of reactive oxygen species (ROS) and triggered mitophagy, but this effect was reversed following the application of ROS scavengers. For the signals mediating mitophagy, the expression of Pink1, but not Bnip3l/Nix or Fundc1, exhibited the most significant changes, which could be counteracted by treatment with a mitochondrial fission inhibitor. Pink1 knockdown suppressed CF activation and mitochondrial fission, which was accompanied by increased CF apoptosis. In conclusion, mitochondrial fission resulted in increased glycolysis and played a crucial role in CF activation. Moreover, mitochondrial fission promoted reactive oxygen species (ROS) production, leading to mitophagy and the consequent degradation of the impaired mitochondria, thus promoting CF survival and maintaining their activation.